THE PARADOX OF CHILD SENTENCING IN MURDER CASES: CRITIQUING THE 'BEST INTERESTS OF THE CHILD' PRINCIPLE IN INDONESIAN COURTS. - Denny Ardian Priambodo; Nurini Aprilianda; Milda Istiqomah (PT. Radja Intercontinental Publishing, 2026)
Criminal offenses are no longer committed only by adults, but also by children, along with the development of technology and social dynamics. Indonesia, through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, provides protection for children in conflict with the law. However, in practice there are still court decisions considered not to have fully applied the principle of the best interests of the child, such as the decision of the Penajam District Court imposing a 20-year sentence and the Lamongan District Court imposing an 11-year sentence. This research is a normative juridical study using a statutory and conceptual approach through library research. The results show that: (1) judges’ considerations are based on both juridical and non-juridical aspects; (2) the application of the best interests of the child principle has not been consistent and has not been fully oriented toward social reintegration; (3) sentencing that is not in accordance with the provisions of the Juvenile Criminal Justice System Law has the potential to damage the child’s future and hinder the fulfillment of the child’s rights, in line with Arif Gosita’s concept of child protection. By examining these two decisions, it becomes important to emphasize that it is recommended to optimize restorative justice, improve the quality of guidance and rehabilitation in Juvenile Development Institutions and Correctional Centers, and strengthen inter-agency collaboration, including the active involvement of child psychologists in court proceedings.